2020
DOI: 10.3390/su122410491
|View full text |Cite
|
Sign up to set email alerts
|

The Climate, Land, Energy, Water and Food Nexus Challenge in a Land Scarce Country: Innovations in the Netherlands

Abstract: The Netherlands has the ambitious target of transitioning to a low-carbon economy by 2050. One factor that may constrain this progress, however, is the large spatial requirements of renewable energy technologies, and resulting competition for land through interlinkages between the Climate (C), Land (L), Energy (E), Water (W) and Food (F) domains—the CLEWF nexus. This study aims at identifying innovations that can improve the performance of the nexus by addressing the land scarcity constraint while supporting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For example, the NexSESF was created by considering the social-ecological system in the FEW nexus [64]. Additionally, the CLEW nexus framework was produced [65] to increase land security. A new framework for water security assessment in Finland was established by using the WEF nexus and considering human well-being, human health, and sustainability of livelihood [66].…”
Section: Overview Of Different Nexus Approaches In the European Count...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the NexSESF was created by considering the social-ecological system in the FEW nexus [64]. Additionally, the CLEW nexus framework was produced [65] to increase land security. A new framework for water security assessment in Finland was established by using the WEF nexus and considering human well-being, human health, and sustainability of livelihood [66].…”
Section: Overview Of Different Nexus Approaches In the European Count...mentioning
confidence: 99%
“…Different scenarios and the SIM4NEXUS game was tested in terms of policies [76] Belgium, Denmark, Germany, Latvia, and Sweden CLEWF nexus Framework A new framework was created [65].…”
Section: Netherland Wef Nexusmentioning
confidence: 99%
“…As literature indicates successful ET and cost-effective NbS are often associated with citizen participation (Van Ham and Klimmek, 2017;Ryghaug et al, 2018). Yet, as some studies state, emerging new technologies often face difficulties in gaining socio-cultural acceptability and deployment which need a social innovation approach or recently used term "sustainable innovation" notions (Hoppe and de Vries, 2018;Janssen et al, 2020). Desa and Jia (2020) define social innovation in relation to sustainability transition as "a set of multi-level mechanisms that facilitate sustainability transitions: across sectors, across social finance, across institutional structures, and through social ventures across geographic regions".…”
Section: Socio-technical Transitionmentioning
confidence: 99%
“…The review found that the land scarcity appears to be one of the key drivers of ET and NbS implementation worldwide (Janssen et al, 2020). Due to a fast urban growth in many countries, public land in cities accounts for a very tiny proportion of total area in comparison to private property and it is suggested that many important issues, such as space for schools, hospitals, and recreation, should be considered for public land rather than NbS (Qiao et al, 2018).…”
Section: Land-energy Relationsmentioning
confidence: 99%
“…Integrating climate change adaptation strategies into the WEF nexus can obtain efficient resource cooperation, resulting in better environmental resilience (Mpandeli et al, 2018). As the nexus approach becomes more and more popular, a lot of research has been published on the WEF nexus concept (Laspidou et al, 2020;Albrecht et al, 2018;Finley and Seiber, 2014;Stephan et al, 2018;Ioannou and Laspidou, 2018), extended Nexus approaches, such as the water-energy-food ecosystem (Malagó et al, 2021), and including land use and climate in the nexus concept (Janssen et al, 2020;Laspidou et al, 2019), with some articles focusing on the combined WEF security and system resilience (Sukhwani et al, 2019;Mguni and van Vliet, 2020). One of the greatest challenges worldwide is to provide essential human needs and resources to all in an environmentally compatible, economically resilient, and socially inclusive manner that is capable to contend with disturbances and catastrophes (Sachs et al, 2019).…”
Section: Introductionmentioning
confidence: 99%